A Retrospective Study of an Updated and Traditional Surgical Approach of the Distally Based Sural Flap - Xu, Heng; Cao, Xuexin; Kiu-Huen, Sally; Zhu, Zhu; Chen, Jun; Chi, Zhenglin; Zhang, Yixin (Journal of Reconstructive Microsurgery, 2020)
Background The distally based sural flap (DBSF) is one of the armamentarium in the lower limb reconstruction. However, the flap has not gained popularity due to concerns about its reliability and donor site morbidity. Based on the anatomy characterization, we combined and developed five modifications to improve the vascular supply and reduce donor site morbidity.Patients and Methods The authors performed a comparison of retrospective study that included patients who underwent either traditional distally based sural flap (tDBSF) or modified distally based sural flap (mDBSF) surgery approach for ankle, heel, and dorsal foot coverage between January 2007 and May, 2019. The five modifications developed to improve the reliability of the flap include: 1. shift the pivot point more proximally 7.0 cm above the lateral malleolus, 2. preserve the lesser saphenous vein and include branches that communicates with the flap, 3. harvest thinner fascial pedicle, 4. change the skin incision to “S” shape, 5. closure of the donor site with a propeller flap.Results Thirty-one patients underwent mDBSF, and 23 received tDBSF. There were no significant differences in the size of the DBSF. Mean pedicle width was significantly narrower in mDBSF (1.63 ± 0.52 cm vs. 3.81 ± 0.70 in tDBSF). The pivot point was also found to be higher in mDBSF (8.01 ± 0.63 cm vs. 5.46 ± 0.56 cm) above the lateral malleolus. In mDBSF, the size of the propeller flap required for donor site closure was 53.45 ± 19.06 cm2 (range 33–80 cm2). The rate of partial necrosis between mDBSF and tDBSF was significantly different (9.68 vs. 34.78%). While the other complications had no difference.Conclusion The modifications applied to the harvesting of the DBSF have achieved higher survival rate, lower dehiscence rate, and shorter hospital stay time in comparison with traditional approach in our retrospective study.
Keywords: distally based sural flap; modification; sequential flap